The Modified Ghost Fluid Method as Applied to Extreme Fluid-Structure Interaction in the Presence of Cavitation (Communications in Computational Physics, 2006)
In this work, the modified Ghost Fluid Method is further developed to apply to compressible fluid coupled to deformable structure, where the pressure in thestructure or flow can vary from an initial extremely high magnitude (such that the solidmedium can be under plastic compression) to a subsequently very low quantity (so thatcavitation can occur in the fluid). New techniques are also developed in the definition ofthe ghost fluid status when the structure is under plastic deformation or when the flowis under cavitation next to the structure. Numerical results show that the improvedMGFM for treatment of the fluid-deformable structure coupling works efficiently forall pressure ranges and is capable of simulating cavitation evolution and cavitation reloading in conjunction with the employment of the isentropic one-fluid cavitation model.
Keywords: Ghost fluid method (GFM); modified ghost fluid method (MGFM); one-fluid cavitation model; cavitation reloading; cavitation-structure interaction.